Effect of teachers' variables on students' academic achievement in entrepreneurship education in technical and vocational colleges in Lagos State, Nigeria - Onikoyi, Olawale Abayomi; Akinnubi, Olaolu Paul; Suleiman, Yusuf; Busari, Jamiu Muhammad; Adeoye, Moses Adeleke (Humanika: Kajian Ilmiah Mata Kuliah Umum, 2025)
This study investigated the effect of teachers' variables on students' academic achievement in entrepreneurship education in technical and vocational colleges in Lagos State, Nigeria. Two research questions and two hypotheses were tested at a 0.05 significance level. The ex-post facto research design was used for the study, and the population of the study was 223 students. The study sample was 85 final-year students from vocational and technical colleges in Ikotun and Ikorodu. No instrument was developed in this study. Rather, a letter was used to request data. Data was analysed using mean for the research questions and ANOVA (Analysis of variance) to test the hypotheses.  The collected data was analysed using the mean for the research questions and ANOVA to test the hypotheses. The finding revealed that the teachers' variables related to sex and certification do not significantly affect student's academic achievement in entrepreneurship education in technical and vocational colleges. The recommendation was made that the government should recruit competent teachers for technical and vocational college teaching; there should be no consideration in recruiting technical and vocational teachers because the students' academic achievement is unrelated to teachers' sex and certification.Penelitian ini menyelidiki pengaruh variabel guru terhadap prestasi akademik siswa dalam pendidikan kewirausahaan di perguruan tinggi teknik dan kejuruan di Negara Bagian Lagos, Nigeria. Dua pertanyaan penelitian dan dua hipotesis diuji pada tingkat signifikansi 0,05. Desain penelitian ex-post facto digunakan untuk penelitian ini, dan populasi penelitian ini adalah 223 mahasiswa. Sampel penelitian adalah 85 siswa tingkat akhir dari sekolah kejuruan dan teknik di Ikotun dan Ikorodu. Tidak ada instrumen yang dikembangkan dalam penelitian ini. Sebaliknya, surat digunakan untuk meminta data. Data dianalisis dengan menggunakan rata-rata untuk pertanyaan penelitian dan ANOVA (Analisis Varians) untuk menguji hipotesis. Data yang terkumpul dianalisis dengan menggunakan rata-rata untuk pertanyaan penelitian dan ANOVA untuk menguji hipotesis. Temuan menunjukkan bahwa variabel guru yang berkaitan dengan jenis kelamin dan sertifikasi tidak secara signifikan mempengaruhi prestasi akademik siswa dalam pendidikan kewirausahaan di perguruan tinggi teknik dan kejuruan. Rekomendasi yang diberikan adalah pemerintah harus merekrut guru yang kompeten untuk mengajar di perguruan tinggi teknik dan kejuruan; tidak perlu mempertimbangkan jenis kelamin dalam merekrut guru teknik dan kejuruan karena prestasi akademik siswa tidak terkait dengan jenis kelamin dan sertifikasi guru.